2012
DOI: 10.1039/c1nj20781d
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ultrasound on porphyrin-based metallogel formation: efficient control of H- and J-type aggregations

Abstract: Efficient control of aggregation modes of the porphyrin-Pd 2+ complexes by ultrasonication and heating is reported. A porphyrinbased metallogel is formed in the presence of Pd 2+ , which displays H-type aggregation. Heating the porphyrin derivative in the presence of Pd 2+ , however, results in J-type aggregation that does not produce a gel. Conclusive evidence was found that the crystal structure of the related porphyrin-Pd 2+ complex obtained by heating shows J-type aggregation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 24 publications
0
23
0
1
Order By: Relevance
“…34 The Fe-C bond lengths of the ferrocene groups and Pd-N bond lengths for the calculated structures were comparable to X-ray determined values (see ESI). 35,36 The large bulky ferrocene groups in PdTFcP distort the porphyrin ring which is evident from the calculated dihedral angles. Minimised structures were also calculated for the radical anion (doublet state) and dianion (singlet state) species.…”
Section: Computational and Mechanistic Considerationsmentioning
confidence: 94%
“…34 The Fe-C bond lengths of the ferrocene groups and Pd-N bond lengths for the calculated structures were comparable to X-ray determined values (see ESI). 35,36 The large bulky ferrocene groups in PdTFcP distort the porphyrin ring which is evident from the calculated dihedral angles. Minimised structures were also calculated for the radical anion (doublet state) and dianion (singlet state) species.…”
Section: Computational and Mechanistic Considerationsmentioning
confidence: 94%
“…Sonogelation of quinacridone derivatives functionalized with urea12d or cholesterol12e,f moieties have been demonstrated by Zhang, Wang, and co‐workers. Moreover, Jung et al., have observed that sonication could modulate the aggregation as well as gelation properties of a porphyrin–palladium(II) complex 12g…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ajayaghosh and Praveen found that OPV derivatives terminated with one or more hydroxyl groups give gels with Jaggregate structures, whereas derivatives terminated with cholesteryl esters produce H-aggregate materials. 226 The balance between H-and J-aggregation may be influenced by environmental changes, such as exposure to heating or sonication, 227 variation in the solvent [228][229][230] or addition of a strongly binding additive. 231 According to Würthner et al, 210 the synthetic route is particularly important when aggregation is governed by non-directional van der Waals interactions, as in the stacking of pseudoisocyanine dyes.…”
Section: Optical Responsesmentioning
confidence: 99%
“…15). 227 The reverse process, conversion from J-to H-aggregates, can be induced through subsequent sonication of the sol. Switching between phases is associated with changes in both colour and fluorescence: the thermally generated metallogel is green and exhibits the non-emissivity typical of H-aggregates, whereas the J-aggregate is red and more strongly fluorescent than both the original gel and the dissolved monomer.…”
Section: Optical Responsesmentioning
confidence: 99%